2011
DOI: 10.1590/s0482-50042011000600008
|View full text |Cite
|
Sign up to set email alerts
|

Influência de elementos meteorológicos na dor de pacientes com osteoartrite: revisão da literatura

Abstract: Despite the frequent assertion that the weather conditions change the intensity of pain in osteoarthritis (OA), this infl uence is controversial and diffi cult to measure. This analysis aims to review articles related to the infl uence of meteorological elements in the OA pain. The literature review was performed with the bibliographical survey databases of the Medical Literature Analysis and Retrieval System Online (MEDLINE) and the Latin American and Caribbean Health Sciences (LILACS), and active search in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 13 publications
0
4
0
4
Order By: Relevance
“…Some studies, although difficult to measure, try to evaluate the influence of weather changes on pain of osteoarthritis patients. Other studies have evaluated if weather conditions could trigger, for instance, migraine 3,4 . Pain may interfere with food intake.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies, although difficult to measure, try to evaluate the influence of weather changes on pain of osteoarthritis patients. Other studies have evaluated if weather conditions could trigger, for instance, migraine 3,4 . Pain may interfere with food intake.…”
Section: Introductionmentioning
confidence: 99%
“…Poucas pesquisas envolvem as variáveis temperatura e clima, sendo estas um motivo de queixa das pessoas com dor crônica 16 . Assim, 43,7% dos usuários perceberam o aumento das suas dores em temperaturas mais baixas e 48,7% em clima úmido, o que sugere uma relação entre temperaturas mais baixas e umidade, gerando assim uma maior contração muscular, compressão ar-ticular e tensão, ocasionando em dores 26 .…”
Section: Resultsunclassified
“…Assim, 43,7% dos usuários perceberam o aumento das suas dores em temperaturas mais baixas e 48,7% em clima úmido, o que sugere uma relação entre temperaturas mais baixas e umidade, gerando assim uma maior contração muscular, compressão ar-ticular e tensão, ocasionando em dores 26 . Porém, ainda são necessários mais estudos na obtenção de evidências relacionadas as atividades diárias e qualidade de vida 16 .…”
Section: Resultsunclassified
See 1 more Smart Citation
“…A systematic review [6] assessed nine studies on weather and rheumatoid arthritis and reported inconsistent results across the studies. Another review [7] stated that recently published studies tend to confirm the association between weather and osteoarthritic pan. Across studies, evidence is still inconsistent and thus, inconclusive.…”
Section: Introductionmentioning
confidence: 99%